Discrimination of epileptogenic lesions and perilesional white matter using diffusion tensor magnetic resonance imaging - Rau, Alexander; Kellner, Elias; Foit, Niels A.; Lützen, Niklas; Heiland, Dieter Henrik; Schulze-Bonhage, Andreas; Reisert, Marco; Kiselev, Valerij G.; Prinz, Marco; Urbach, Horst; Mader, Irina (Neuroradiology Journal, 2019)
The aim of this study was to evaluate whether ganglioglioma (GGL), dysembryoplastic neuroepithelial tumour (DNET) and FCD (focal cortical dysplasia) are distinguishable through diffusion tensor imaging. Additionally, it was investigated whether the diffusion measures differed in the perilesional (pNAWM) and in the contralateral normal appearing white matter (cNAWM). Six GGLs, eight DNETs and seven FCDs were included in this study. Quantitative diffusion measures, that is, axial, radial and mean diffusivity and fractional anisotropy, were determined in the lesion identified on isotropic T2 or FLAIR-weighted images and in pNAWM and cNAWM, respectively. DNET differed from FCD in mean diffusivity, and GGL from FCD in radial diffusivity. Both types of glioneuronal tumours were different from pNAWM in fractional anisotropy and radial diffusivity. For identifying the tumour edges, threshold values for tumour-free tissue were investigated with receiver operating characteristic analyses: tumour could be separated from pNAWM at a threshold ≤ 0.32 (fractional anisotropy) or ≥ 0.56 (radial diffusivity) *10–3 mm2/s (area under the curve 0.995 and 0.990 respectively). While diffusion parameters of FCDs differed from cNAWM (radial diffusivity (*10–3mm/s2): 0.74 ± 0.19 vs. 0.43 ± 0.05; corrected p-value < 0.001), the pNAWM could not be differentiated from the FCD.
CRIS-Team Scopus Importer:2024-03-07
Keywords: diffusion tensor imaging; Epilepsy associated lesions; focal cortical dysplasia; long-term epilepsy-associated tumours; MRI